Awareness, Care and Treatment In Obesity maNagement to inform Haemophilia Obesity Patient Empowerment (ACTION‐TO‐HOPE): Results of a survey of US patients with haemophilia and obesity (PwHO) and their partners and caregivers. (3rd February 2020) - Croteau, Stacy E.; Cutter, Susan; Hernandez, Grace; Wicklund, Brian; Dreyer Gillette, Meredith L.; Haugstad, Kimberly; Cooper, David L.; Ostrow, Vlady; Nadglowski, Joe
Abstract: Background: The ACTION study identified barriers to initiating and maintaining weight loss in patients with obesity; however, joint‐related issues (pain, mobility and bleeding) may affect perceptions of patients with haemophilia and obesity (PwHO). Aim: To identify patient and caregiver insights on the unique challenges of PwHO. Methods: Following IRB approval, adults who self‐identified as PwHO, spouses/partners of adult PwHO, and caregivers of adolescent PwHO (aged 12‐17 years) completed an online survey between December 2017 and April 2018. Results: Respondents included 124 adult PwHO, 45 spouses/partners and 42 caregivers. By calculated BMI, most adults were overweight (43%) or had obesity (51%); this differed from self‐reported weight category. PwHO goals were improving health conditions (60%), having more energy (54%), reducing risks of weight (46%), and losing any weight (44%). Issues related to joint health were secondary for PwHO but frequently reported by spouses/parents. Most perceived weight loss to be a high priority (66%) and their responsibility (64%) but required a complete lifestyle change (63%). Most anticipated that weight loss would reduce joint pain (62%), bleeding (58%) and factor use (52%) and increase mobility (62%). Weight discussions with healthcare providers (HCPs) were commonly reported (51%). HCP discussions targeted improving health conditions (46%), achieving any weight loss (44%), being more active (73%) and improving eating habits (72%). Most PwHO (65%) perceived obesity as a disease and believe that 10% weight loss would be extremely beneficial (78%). In the past 5 years, 80% discussed being overweight and 68% losing weight; a minority reported being successful (9%) or somewhat successful (38%) with weight loss. More realistic or specific (51%/47%) goals, resources (46%), referrals to weight‐loss programmes (41%) or dietitians (38%), meals or recipes (54%/50%), local or national (42%/41%) programmes for PwHO and success stories of PwHO (40%) are needed or would be helpful. Conclusions: PwHO, spouse/partners and caregivers exhibited awareness of general and haemophilia‐specific consequences of excess body weight. Most have tried general approaches to improve eating and increase activity with little success and desire more education on weight management and more details on specific actionable recommendations distributed through existing haemophilia channels. These insights will better inform the creation of weight‐loss programmes for this community.